Treating mood disorders in patients with a history of intestinal surgery: a systematic review. (May 2015) - Lloret-Linares, Célia; Bellivier, Frank; Heron, Kyle; Besson, Marie
Abstract : Bariatric surgery is increasingly being performed, with the intended benefits of significant and durable weight loss. Radical surgical resection can result in short bowel syndrome (SBS), a rare and devastating condition. Psychological distress is common in these patients. Relevant articles were identified by searching Pubmed and EMBASE databases with the following keywords: 'Bariatrics'[Mesh] OR 'Short Bowel Syndrome' AND 'Antidepressive Agents' OR 'Psychotropic Drugs'[Mesh]. One in-vitro study, four clinical studies and six relevant case reports were identified. Most clinical studies on antidepressant focused on the Roux-en-Y gastric bypass (RYGB); [ZERO WIDTH SPACE][ZERO WIDTH SPACE]these results are somewhat conflicting for a variety of reasons including different methodologies and small sample sizes. One month after RYGB, in patients receiving serotonin or serotonin/noradrenaline reuptake inhibitors, antidepressant levels decrease to 50% of preoperative levels and return to baseline (or greater) by 6 months in almost all patients. Other pharmacokinetic studies have shown that, 1 year after RYGB, duloxetine and sertraline levels are significantly reduced in comparison with the control population. Paradoxically, in patients with SBS and a few years after surgery, high concentration to dose ratios have been reported for citalopram and escitalopram; this may be because of an intestinal adaptation. Surgery of the intestine is likely to modify absorption and first-pass metabolism of drugs; managing the treatment of depression and anxiety in bariatric and SBS patients therefore presents a major challenge. Close clinical follow-up, associated with therapeutic drug monitoring when available, should enable the optimization of treatment response and modulate the risk of adverse events.